Dignity and defiance : stories from Bolivia's challenge to globalization - Shultz, Jim; Draper, Melissa (University of California Press, 2008)
Dignity and Defiance is a powerful, eyewitness account of Bolivia's decade-long rebellion against globalization imposed from abroad. Based on extensive interviews, this story comes alive with first-person accounts of a massive Enron/Shell oil spill from an elderly woman whose livelihood it threatens, of the young people who stood down a former dictator to take back control of their water, and of Bolivia's dramatic and successful challenge to the policies of the World Bank and the International Monetary Fund. Featuring a substantial introduction, a conclusion, and introductions to each of the c.